Peran Dinas Kelautan dan Perikanan Kabupaten Kepulauan Anambas dalam Perlindungan Ikan Napoleon (Studi di Desa Air Sena Kecamatan Siantan Tengah) - Billy Jenawi, Ferizone, Ana Jemi (Dialektika Publik, 2019)
Napoleon fish is one of the types of fish that have a high economic value. Kepulauan Anambas is one of the regions in Indonesia which has a population of Napoleon fish the most. To protect the fish from extinction Government was published a decision of the Minister of Marine and Fisheries the number 37 Year 2013 regarding the determination of the Status of the protection of Napoleon. To view the roles carried out by the Department of Marine and Fisheries Kepulauan Anambas used theory of the role from Siagian with the indicator stabilizer, innovators, modernisator, pioneer and implementors. Type of research is qualitative with descriptive analysis techniques. The results of this research show that the role of the Department of Marine and Fisheries was keep order fishers in the protection of Napoleon fish by making policies to maintain fisherman economic stability and fishermen by creating joint ventures. Role as innovator, Department of marine and Fisheries have made special location fish protection Napoleon and applied cultivation grouper so not just farmed fish of Napoleon. As modernisator the Marine and Fisheries Agency has not used a technology that could help in the Napoleon fish farming but the Office of maritime and Fishery will make Napoloen fish as one of the tourist attractions. His role as a pioneer, Marine and Fisheries Agency has delivered fishing aspirations and also increase public awareness through socialization. As executor, Department of marine and Fisheries surveillance has been instrumental in the capture and exportation